2006
DOI: 10.1210/jc.2005-2282
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Primary Hyperparathyroidism on the Oral Cavity

Abstract: Changes in the oral cavity observed in patients with HPT suggested both decreased cortical density and increased likelihood of oral tori. The contemporary oral manifestations of primary HPT are different from those previously reported, and health care providers should be aware of newer, more subtle findings that may be present when treating patients with HPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 35 publications
3
52
0
3
Order By: Relevance
“…Ardine et al 71 reported that patients with bisphosphonate-associated ONJ had persistently higher PTH levels compared to controls without ONJ and they suggested that high PTH may be involved in the pathogenesis of ONJ. Evidence against this theory is that in patients with primary hyperparathyroidism and elevated PTH, lesions in the oral cavity include reduced radicular lamina dura, reduced interdental alveolar bone density and reduced cortical bone at the gonial index, 72 whereas the bisphosphonate-associated ONJ is characterized by osteopetrosis-like osseous sclerosis with thickening of the lamina dura and of the alveolar crest and sclerosis of the alveolar margin. 73 …”
Section: Osteonecrosis Of the Jawmentioning
confidence: 99%
“…Ardine et al 71 reported that patients with bisphosphonate-associated ONJ had persistently higher PTH levels compared to controls without ONJ and they suggested that high PTH may be involved in the pathogenesis of ONJ. Evidence against this theory is that in patients with primary hyperparathyroidism and elevated PTH, lesions in the oral cavity include reduced radicular lamina dura, reduced interdental alveolar bone density and reduced cortical bone at the gonial index, 72 whereas the bisphosphonate-associated ONJ is characterized by osteopetrosis-like osseous sclerosis with thickening of the lamina dura and of the alveolar crest and sclerosis of the alveolar margin. 73 …”
Section: Osteonecrosis Of the Jawmentioning
confidence: 99%
“…Classic skeletal lesions, which are bone resorption, bone cysts, brown tumours and generalized osteopenia, occur in less than 5% of cases. [31] …”
Section: Metabolic Lesions Hyperparathyroidismmentioning
confidence: 99%
“…It may be seen in patients with either primary or secondary hyperparathyroidism. [31] www.wjpps.com [31]…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, several cases of brown tumor that did not disappear or even grew after normalization of HPT level have been reported. In these cases brown tumor resection should be the preferred treatment (8,9,(13)(14)(15).…”
Section: Oral Manifestations and Dental Management Of Patients With Pmentioning
confidence: 99%